Unregulated Self-Preferencing in ASEAN Digital Platform Ecosystems - Lu Sudirman; David Tan; Windi Afdal; Nur Fatihah; Rufinus Hotmaulana Hutauruk (Syura: Journal of Law, 2026)
The rapid expansion of digital platforms in Southeast Asia has intensified concerns regarding self-preferencing practices within vertically integrated ecosystems, which often operate in opaque and difficult-to-detect forms. This study examines the inadequacy of existing antitrust frameworks in Indonesia, the Philippines, and Vietnam in addressing such anti-competitive conduct. The research aims to assess the normative sufficiency of these legal systems and identify regulatory gaps in tackling self-preferencing in digital markets. This study employs a doctrinal legal research method combined with a comparative approach. The findings reveal that all three jurisdictions face significant limitations, particularly due to the absence of explicit prohibitions on self-preferencing mechanisms to address algorithmic bias, particularly in its early stage. Indonesia demonstrates the most substantial deficiencies, while the Philippines and Vietnam offer relatively more flexible interpretative tools, albeit still insufficient in addressing the complexities of digital ecosystems. The study concludes that the current, primarily ex-post approach in the relevant frameworks needs to be supported by an ex-ante mechanism, which leads the study to recommend the introduction of explicit legal recognition of self-preferencing and expansion of vertical integration provisions, along with other safeguards to prevent further competitive damage from self-preferencing.